New Frontier on Antimicrobial Therapy: Long-Acting Lipoglycopeptides - Valentina Siciliano; Flavio Sangiorgi; Pierluigi Del Vecchio; Layla Vahedi; Maya Manuela Gross; Angela Saviano; Veronica Ojetti (Pathogens, 2024)
Long-acting lipoglycopeptides (LGPs), such as dalbavancin and oritavancin, are semisynthetic antibiotics known for their strong effectiveness against a wide array of Gram-positive bacteria. This includes Staphylococcus aureus, both methicillin-sensitive (MSSA) and methicillin-resistant (MRSA) strains, coagulase-negative Staphylococci (CoNS), streptococci, and vancomycin-sensitive Enterococcus faecalis. A literature search was conducted on PubMed and on ClinicalTrials.gov to identify articles published until July 2023 investigating the use of oritavancin and dalbavancin in clinical practice. The review included case reports, case series, observational studies, and clinical studies. Although more consistent data are needed, LGPs seem to be a good alternative that may provide a quicker hospital discharge and reduce long-term intravenous access and therapy. This is attributed to their unique pharmacologic and pharmacokinetic characteristics. More quality data (i.e., number of patients treated with clinical success) are needed before clinicians may use these therapies more widely.